Strategy for Developing Organisational Culture in the Public Organisation of Research and Development in Indonesia - Suyatno (Advances in Social Sciences Research Journal, 2022)
This Paper focuses on the strategy of developing organizational culture in the public Research and Development Organization. The aim of the research is to know the strategy for developing organisational culture in R & D organisation in Indonesia. The study uses qualitative approach. It starts exploring the topic of organisational culture, collecting the data, then describes the phenomenon occurs in the organisations, analyses based on the theory and makes conclussion. Informants of this study were the stakeholders involved in the organization of R & D in the Ministry, University, Pure Research and Development Organization, and Local Government Research and Development. The primary data were obtained through observation, interviews to the informants and discussion with the stake holders involved in the organisation of Research and Development. Secondary data were obtained from written documents of the organisations. The data is collected from 2 prominent Higher Education Research and Development, 2 Local Government Research and Development, 2 Ministry Research and Development, and 2 Pure Research and Development organisations in Indonesia. The Strategy for developing the value, norm and belief of the organization is developing, instilling and sharing to the members through the activities of the main business of the organization to obtain the realization of the organization vision and mission. The process of instilling and making habit working culture in the public R and D in Indonesia is based on regulation.